2015
DOI: 10.1016/j.celrep.2015.11.060
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Prion [SWI+] Abolishes Multicellular Growth by Triggering Conformational Changes of Multiple Regulators Required for Flocculin Gene Expression

Abstract: Summary While transcription factors are prevalent among yeast prion proteins, the role of prion-mediated transcriptional regulation remains elusive. We show here that the yeast prion [SWI+] abolishes flocculin (FLO) gene expression and results in a complete loss of multicellularity. Further investigation demonstrates that besides Swi1, multiple other proteins essential for FLO expression, including Mss11, Sap30, and Msn1 also undergo conformational changes, and become inactivated in [SWI+] cells. Moreover, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 69 publications
3
58
0
Order By: Relevance
“…The beneficial phenotypes conferred by yeast prions are often observed under stress conditions, which has led to the suggestion that yeast prions constitute bet-hedging devices, which can reveal potentially adaptive genetic diversity in fluctuating environments (Du et al, 2015; Garcia and Jarosz, 2014; Halfmann et al, 2010; Halfmann and Lindquist, 2010; Masel and Bergman, 2003; Newby and Lindquist, 2013; Tyedmers et al, 2008). This process is facilitated by the conformational range of PrDs, which can access multiple, distinct cross-β structures or strains (Shorter, 2010).…”
Section: Prions As Epigenetic Regulators In Yeastmentioning
confidence: 99%
“…The beneficial phenotypes conferred by yeast prions are often observed under stress conditions, which has led to the suggestion that yeast prions constitute bet-hedging devices, which can reveal potentially adaptive genetic diversity in fluctuating environments (Du et al, 2015; Garcia and Jarosz, 2014; Halfmann et al, 2010; Halfmann and Lindquist, 2010; Masel and Bergman, 2003; Newby and Lindquist, 2013; Tyedmers et al, 2008). This process is facilitated by the conformational range of PrDs, which can access multiple, distinct cross-β structures or strains (Shorter, 2010).…”
Section: Prions As Epigenetic Regulators In Yeastmentioning
confidence: 99%
“…Although published data showed that these UASs within the FLO11 promoter could respond independently to diverse external and internal signals, determination of the SWI/SNF‐acting UASs was reported to be difficult (Rupp et al ., ; Braus et al ., ; Basu et al ., ). Since Swi1 is required to activate FLO11 gene expression (Basu et al ., ; Du et al ., ), we assumed that the SWI/SNF (thus, Swi1)‐acting sites are within the previously identified UASs but not URSs. To identify Swi1‐acting sites, we generated six truncated FLO11 upstream regulatory region containing various numbers of UASs (+) and/or URSs (‐) by PCR (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S3). As we showed previously (Du et al ., ), Chr::P FLO1 ‐URA3 can clearly distinguish [ SWI + ] and [ swi ‐ ] cells in both ‐uracil and +5‐FOA assays (Supporting Information Fig. S3) and thus it is, applicable as a useful [ SWI + ] reporter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prion formation leads to DNA-independent changes in heritable traits in microorganisms such as Saccharomyces cerevisiae and Podospora anserina [2,3]. For example, [ PSI + ] and [ ISP + ] prions, whose structural proteins are Sup35 and Sfp1, respectively, modulate nonsense suppression [2,4]; Swi1 in its prion state, [ SWI + ], causes a partial loss of function in utilizing non-glucose sugars and completely abolish yeast multicellularity [5,6], while Ure2 in its [ URE3 ] form changes nitrogen catabolism [2]. The HET-s protein of P .…”
Section: Introductionmentioning
confidence: 99%